PENGARUH MEDIA PEMBELAJARAN DAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR GEOGRAFI - Mulya Sari; Sumadi Sumadi; Zulkarnain Zulkarnain (JPG (Jurnal Penelitian Geografi), 2014)
This study aims to find out (1) the effect of learning media on learning outcomes on the subjects of geography, (2) the effect of learning independence on learning outcomes on the subjects of geography, (3) the effect of learning media and learning independence collectively on learning outcomes on the subjects of geography. The research is using ex post facto. The population in this research is the social science students of class XI with 135 students, with a sample of 100 students. The result showed (1) learning media effect on student learning outcomes on the subjects of geography, the contribution of the effectis about 30 percent,(2) independence learning effect on student learning outcomes on the subjects of geography, the contribution of the effect is about 20,9 percent,(3) learning media and learning independence collectively effect on student learning outcomes on the subjects of geography, the contribution of the effect is about 33,9 percent.Penelitian ini bertujuan untuk mengetahui (1) pengaruh media pembelajaran terhadap hasil belajar geografi, (2) pengaruh kemandirian belajar terhadap hasil belajar geografi, (3) pengaruh media pembelajaran dan kemandirian belajar terhadap hasil belajar geografi. Penelitian menggunakan metode ex post facto. Populasi dalam penelitian ini adalah siswa kelas XI IPS sejumlah 135 siswa, dengan sampel penelitian sebesar 100 siswa. Hasil penelitian menunjukkan bahwa (1) media pembelajaran berpengaruh terhadap hasil belajar geografi, besarnya sumbangan pengaruh yaitu 30 persen, (2) kemandirian belajar berpengaruh terhadap hasil belajar geografi, besarnya sumbangan pengaruh yaitu 20,9 persen, (3) media pembelajaran dan kemandirian belajar berpengaruh terhadap hasil belajar geografi, besarnya sumbangan pengaruh yaitu 33,9 persen.Kata kunci: hasil belajar, kemandirian belajar, media pembelajaran